Altered frequency and function of spleen CTLA-4+Tim-3+ T cells are associated with miscarriage. Issue 2 (26th April 2019) - Wang, Songcun; Li, Mengdie; Sun, Fengrun; Chen, Chunqin; Ye, JiangFeng; Li, Dajin; Qian, Jinfeng; Du, Meirong
Abstract: Normal pregnancy is associated with several immune adaptations in both systemic and local maternal–fetal interface to allow the growth of semi-allogeneic conceptus. A failure in maternal immune tolerance to the fetus may result in abnormal pregnancies, such as recurrent spontaneous abortion. The regulation of T-cell homeostasis during pregnancy has important implications for maternal tolerance and immunity. Cytotoxic T-lymphocyte antigen-4 (CTLA-4) and T-cell immunoglobulin mucin-3 (Tim-3) are important negative immune regulatory molecules involved in viral persistence and tumor metastasis. Here we described the lower frequency of splenic T cells co-expressing CTLA-4 and Tim-3 accompanied by higher levels of proinflammatory but lower anti-inflammatory cytokines production in abortion-prone mouse model. Blockade of CTLA-4 and Tim-3 pathways leaded to the dysfunction of splenic T cells. By the higher expression during normal pregnancy, CTLA-4 and Tim-3 co-expression on splenic T cells linked to immunosuppressive phenotype. As the spleen is an important site for peripheral immune activation, our data suggest potential noninvasive biomarkers and therapeutic targets for miscarriage. Abstract : The lower frequency of splenic T cells co-expressing CTLA-4 and Tim-3 accompanied by altered cytokines production is associated with miscarriage.